Myriophyllum aquaticum (Vell.) Verdc. (Haloragaceae): A new angiospermic record for Bangladesh - Alfasane, Md. Almujaddade; Akhtar, Ashika; Mehnaz, Maliha; Ayesha, Mst.; Begum, Z.N. Tahmida (Bangladesh Journal of Plant Taxonomy, 2019)
Not available.